Sustainable Wastewater Treatment: Recent Progress in the use of Bio-Waste-Derived Adsorbents for Organic Dye Removal - Samuel, Humphrey Sam; Okino, Isah Adeiza; Okibe, Gideon; Etim, Emmanuel Edet (Asian Journal of Environmental Research, 2024)
There are serious health and environmental hazards associated with the growing amount of organic dyes in wastewater from sectors like food processing, leather, and textiles. These pollutants are frequently ineffectively removed by traditional wastewater treatment techniques. Adsorbents made from bio-waste have become a viable substitute because of their high removal efficiency, affordability, and sustainability. The adsorption of organic dyes is facilitated by the distinct surface chemistries of these adsorbents, which are made from a variety of biomass sources. Through synthesis and modification approaches, recent research has concentrated on enhancing these materials' adsorption capacity, selectivity, and overall performance. Adsorbents made from bio-waste have potential uses in pollutant degradation, nutrient recovery, and value addition in addition to dye removal. But issues like leaching and long-term stability need to be carefully thought out.  This review highlights the recent advancements in the application of bio-waste-derived adsorbents for organic dye removal from wastewater, emphasizing their potential contributions to sustainable wastewater treatment and resource recovery.